Evolving Role of Transcatheter Valve Replacement for the Treatment of Severe Aortic Stenosis. Issue 1 (2nd January 2020) - Boukhris, Marouane; Forcillo, Jessica; Potvin, Jeannot; Gobeil, Jean-François; Noiseux, Nicolas; Stevens, Louis-Mathieu; Hillani, Ali; Masson, Jean-Bernard
ABSTRACT: Over the last 10 years, transcatheter aortic valve replacement (TAVR) has gained acceptance for patients at prohibitive, high and intermediate risk for surgical aortic valve replacement (SAVR). Recent evidence supports the utilization of TAVR in low surgical risk patients: two independent randomized trials have demonstrated short and mid-term clinical benefits of transfemoral TAVR over SAVR for endpoints such as all-cause mortality, stroke, and re-hospitalizations. The aim of the current manuscript is to provide an overview of the most important randomized clinical trials comparing TAVR with SAVR according to surgical risk, discuss the remaining challenges of TAVR and identify patients in whom open surgery remains the best practice in presence of severe AS. We also discuss how the emergence of TAVR as a suitable alternative for low-risk patients changes the Heart Team evaluation and treatment selection process.